User Engagement and Activism on the DACA Hashtag: An Analysis of Tweets - Sandhya Rao; Daniel Carter; Vanessa de Macedo Higgins Joyce; Eun Jeong Lee (Norteamérica)
Deferred Action for Childhood Arrivals directly impacts about 700,000 people residing in the United States, most of whom immigrated from Mexico. This research presents a content analysis of tweets from the DACA hashtag on three crucial days pertaining to ending DACA, examining stakeholders’ uses of the hashtag and engagement with it. Results showed significant differences in the level of engagement by different stakeholders but not between those who supported, opposed or were neutral toward DACA. However, there were significant differences between the different stakeholders as well as between the groups with regards to call for action. The study provides a better understanding of user engagement and activism via Twitter in public debate that could potentially result in policy changes.